2003
DOI: 10.1095/biolreprod.102.005520
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor-Receptor Tyrosine Kinase Activity Regulates Expansion of Porcine Oocyte-Cumulus Cell Complexes In Vitro1

Abstract: We have recently shown that epidermal growth factor (EGF) strongly stimulates expansion of porcine oocyte-cumulus complexes (OCCs) isolated from large follicles (>6 mm) and does not promote expansion of OCCs from small (3-4-mm) follicles. In order to elucidate the role of EGF in OCCs expansion, in the present study, we first examined the presence of EGF receptors (EGFRs) in cumulus cells isolated from follicles of different sizes. Surprisingly, immunoblotting showed that cumulus cells obtained from all follicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 53 publications
2
56
0
2
Order By: Relevance
“…EGFR tyrosine kinase and MAPK3/1 activities are crucial for expansion of cumulus cells in different species including the pig (Prochazka et al 2003. Nevertheless, the data of this study indicate that EGFR/MAPK3/1 pathway is not the only pathway controlling gonadotropininduced expression of the expansion-related genes, at least in the in vitro system.…”
Section: Signaling In Pig Cumulus-oocyte Complexesmentioning
confidence: 69%
“…EGFR tyrosine kinase and MAPK3/1 activities are crucial for expansion of cumulus cells in different species including the pig (Prochazka et al 2003. Nevertheless, the data of this study indicate that EGFR/MAPK3/1 pathway is not the only pathway controlling gonadotropininduced expression of the expansion-related genes, at least in the in vitro system.…”
Section: Signaling In Pig Cumulus-oocyte Complexesmentioning
confidence: 69%
“…However, our current study opens up the possibility that granulosa and/or cumulus cells might regulate their responsiveness throughout folliculogenesis to oocyte factors such as GDF9 by modulating the basal or autocrine level of EGF receptor activity and resulting ERK1/2 phosphorylation. In support of the latter concept, Prochazka and collaborators (Prochazka et al, 2003) have shown that with progressive differentiation of pig cumulus cells through antral folliculogenesis, there is functional maturation of the EGFR. SFKs might play a key role in that context since it has been shown to act both upstream 3173 GDF9 requires ERK1/2 in granulosa cells and downstream of EGFR and to participate in its signal transduction (Bobe et al, 2003;Schauwienold et al, 2008).…”
Section: Journal Of Cell Science 123 (18)mentioning
confidence: 89%
“…We have shown in previous papers that the EGFR signaling plays an important role in the regulation of meiosis in the pig (Prochazka et al 2000(Prochazka et al , 2003. The aim of this work was to answer the question of whether EGF-like peptides can substitute for gonadotropins in stimulation of cumulus expansion, oocyte maturation, and acquisition of developmental competence in vitro or whether additional gonadotropin-induced signaling, besides the induction of the EGF-like peptides, is essential for occurrence of these events in pig COCs.…”
Section: Introductionmentioning
confidence: 99%